Data science and big data analytics: discovering, analyzing, visualizing and presenting data. (Hoboken, New Jersey : John Wiley & Son, Inc., 2015)
Data Science and Big Data Analytics is about harnessing the power of data for new insights. The book covers the breadth of activities and methods and tools that Data Scientists use.
Chapter 1. Introduction to big data analysis -- Chapter 2. Data analytics lifecycle -- Chapter 3. Review of basic data analytic methods using R -- Chapter 4. Advanced analytical theory and methods : clustering -- Chapter 5 . Advanced analytical theory and methods : association rules -- Chapter 6. Advanced analytical theory and methods : regression -- Chapter 7. Advanced analytical theory and methods : classification -- Chapter 8. Advanced analytical theory and methods : Time series analysis -- Chapter 9. Advanced analytical theory and methods : Text analysis -- Chapter 10. Advanced analytics - technology and tools : MapReduce and hadoop -- Chapter 11. Advanced analytics - technology and tools : In-database analytics -- Chapter 12. The endgame, or putting it all together
Includes bibliographical references and index.
Keywords: DATA ANALYSIS